Human leukemia antigen-A*0201-restricted epitopes of human endogenous retrovirus W family envelope (HERV-W env) induce strong cytotoxic T lymphocyte responses - Tu, Xiaoning (Virol Sin, 2017)
Human endogenous retrovirus W family (HERV-W) envelope (env) has been reported to be related to several human diseases, including autoimmune disorders, and it could activate innate immunity. However, there are no reports investigating whether human leukemia antigen (HLA)-A*0201(+) restriction is involved in the immune response caused by HERV-W env in neuropsychiatric diseases. In the present study, HERV-W env-derived epitopes presented by HLA-A*0201 are described with the potential for use in adoptive immunotherapy. Five peptides displaying HLA-A*0201-binding motifs were predicted using SYFEPITHI and BIMAS, and synthesized. A CCK-8 assay showed peptides W, Q and T promoted lymphocyte proliferation. Stimulation of peripheral blood mononuclear cells from HLA-A*0201(+) donors with each of these peptides induced peptide-specific CD8(+) T cells. High numbers of IFN-γ-secreting T cells were also detectable after several weekly stimulations with W, Q and T. Besides lysis of HERV-W env-loaded target cells, specific apoptosis was also observed. These data demonstrate that human T cells can be sensitized toward HERV-W env peptides (W, Q and T) and, moreover, pose a high killing potential toward HERV-W env-expressing U251 cells. In conclusion, peptides W Q and T, which are HERV-W env antigenic epitopes, have both antigenicity and immunogenicity, and can cause strong T cell immune responses. Our data strengthen the view that HERV-W env should be considered as an autoantigen that can induce autoimmunity in neuropsychiatric diseases, such as multiple sclerosis and schizophrenia. These data might provide an experimental foundation for a HERV-W env peptide vaccine and new insight into the treatment of neuropsychiatric diseases.